PENDEKATAN KOMUNIKATIF DALAM PENGAJARAN BAHASA ARAB - Putri Hardiyanti; Tomi Enramika; Zakiyatunnisa Al Mubarokah (Pendidikan Bahasa Arab FTK UIN Sulthan Thaha Saifuddin Jambi, 2024)
This article aims to find out how the communicative approach can be used as an approach in teaching Arabic, especially in teaching Arabic for foreign speakers. The aim to be achieved in writing this article is to explain communicative language teaching related to communicative competence, the concept of language teaching with a communicative approach, assumptions, characteristics and things that are included in Arabic language teaching. The communicative approach or communicative language teaching is based on linguistic theory which states that language is a tool for communication. The communicative approach is based on the assumption that every human being has an innate ability called a